Determination of patient satisfaction at accredited antiretroviral treatment sites in the Gert Sibande District, Mpumalanga Province - Ogunsanwo, Damilola Akinkunle (University of Limpopo (Medunsa Campus), 2012)
CHAPTER 1 INTRODUCTION 1.1 INTRODUCTION This chapter presents the background and rationale for the study followed by the problem statement. The aim and objectives of the study as well as the significance of the study will also be explained. 1.2 BACKGROUND AND RATIONALE FOR THE STUDY In the past decade, patient satisfaction has become an important performance and outcome measure of health care (Moret, Nguyen, Pillet, Faissard, Lombrail & Gasquet, 2007). Although high levels of patient satisfaction are important for a successful strategy against Human Immuno-deficiency Virus/Acquired Immune Deficiency Syndrome (HIV/AIDS), research into patient satisfaction with health care services in general, and with antiretroviral treatment (ART) services in particular, has been limited in South Africa (Myburgh, Solanki, Smith & Lalloo, 2005). In a weakened healthcare system, it is even more crucial to ensure a high quality of care and patient satisfaction to maximise the benefits of scarce resources. In addition, patient views on the quality of public sector antiretroviral (ARV) care are relatively unexplored (Igumbor, 2003; Myburgh et aI., 2005). The assessment of satisfaction among hospitalised patients is increasingly recognised as a major component of quality management in patient care. Continuous quality improvement, comparison of hospital performances and demands for accountability are some of the reasons that lead hospitals to measure patient satisfaction (Ross, Steward & Sinacore, 1995). As has been observed in many industrialised countries, the provision of ART via public health systems, can transform AIDS from a fast, insidious killer into a more manageable, though still incurable, chronic illness (Abdool Karim, 2005). However, in resource-limited settings, there are many challenges in successfully scaling-up ART and reorienting service delivery towards chronic disease care. Shortages in human resources for healthcare are often cited as the most important obstacle to a specific for all ART sites in the province should be developed and monitored. A long term strategy to address the critical shortage of healthcare professionals should be developed by provincial policy makers which will in the long run reduce long waiting times experienced by our clients.
Thesis(MSc(Med)(Pharmacy))--University of Limpopo, 2012.
Keywords: Antiretroviral treatment